Analisis Hukum Ekonomi Syariah Terhadap Jual Beli Aset Kripto (Cryptocurrency) Sebagai Komoditas Perdagangan Digital - Randy Angga Putra Mu'awanah; Mu’awanah Mu’awanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of financial technology has driven the emergence of crypto assets as commodities in digital trading, which is also growing in Indonesia. However, their existence still raises differing perspectives within Islamic economic law. This study aims to analyze the trading of crypto assets as digital commodities based on sharia principles, particularly concerning the clarity of the contract object, the validity of transactions, and the potential presence of elements such as gharar (uncertainty), maysir (gambling), and riba (usury). Accordingly, this research employs a literature-based approach, examining the Qur’an, Hadith, jurisprudential maxims, fatwas, and regulations. The results indicate that crypto assets are not permissible as a means of payment under sharia law; however, they may be allowed as digital commodities provided they meet the principles of transparency, do not involve excessive speculation, and align with the values of justice and public benefit (maslahah).